English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-11-12 13:27:46 · 4 answers · asked by wanda_brown62 1 in Science & Mathematics Mathematics

4 answers

Combine like terms, so n-2n = -n

n - 2n = -14

-n = -14

n = 14

Pretty straightforward. What part messed you up? Let us know and I (we) will try to explain for you.

NRT

2006-11-12 13:29:37 · answer #1 · answered by New Rule Tomorrow 2 · 0 0

n-2n= -14
-n = -14
n = 14

2006-11-12 21:30:28 · answer #2 · answered by bourqueno77 4 · 0 0

n-2n= -14
-n= -14
n=14

2006-11-12 21:30:31 · answer #3 · answered by Phy A 5 · 0 0

n - 2n = -14

Put the two n-values together...

-n = -14

Multiply both sides by -1...

n = 14

And there you go...

2006-11-12 21:30:47 · answer #4 · answered by scarletcub11 3 · 0 0

fedest.com, questions and answers